1980
DOI: 10.1111/j.1600-0447.1980.tb00585.x
|View full text |Cite
|
Sign up to set email alerts
|

A collaborative study of genetic linkage of bipolar manic‐depressive illness and red/green colorblindness : A PROJECT OF THE BIOLOGICAL PSYCHIATRY COLLABORATIVE PROGRAM OF THE WORLD HEALTH ORGANIZATION

Abstract: A study of linkage of bipolar manic-depressive illness to the protan/deutan colorblindness region of the X-chromosome was performed on 16 informative families, in a WHO collaborative study (eight families from Brussels, Six from Bethesda, one each from Basel and Copenhagen). Overall, the series did not support close linkage, but is possibly suggestive of loose linkage. The possibility of genetic heterogeneity of bipolar manic-depressive illness, with one form linked to colorblindness, is considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The finding was supported by evidence for linkage between manic-depressive illness and color blindness (protanopia and deuteranopia) (Xq28) [Baron, 1977;Mendlewicz et al, 1979], although the evidence for linkage was not universal [Gershon et al, 1979[Gershon et al, , 1980. Eventually glucose-6-phosphate dehydrogenase (G6PD), a biochemical marker encoded by a gene on Xq28, was subjected to linkage studies and revealed a lod score of 4.32 in a large family of Persian Sephardic Jewish origin segregating both BD and G6PD deficiency .…”
Section: Bd and X Chromosomementioning
confidence: 73%
“…The finding was supported by evidence for linkage between manic-depressive illness and color blindness (protanopia and deuteranopia) (Xq28) [Baron, 1977;Mendlewicz et al, 1979], although the evidence for linkage was not universal [Gershon et al, 1979[Gershon et al, , 1980. Eventually glucose-6-phosphate dehydrogenase (G6PD), a biochemical marker encoded by a gene on Xq28, was subjected to linkage studies and revealed a lod score of 4.32 in a large family of Persian Sephardic Jewish origin segregating both BD and G6PD deficiency .…”
Section: Bd and X Chromosomementioning
confidence: 73%